Drawn to change : graphic histories of working-class struggle - Buhle, Paul 1944-; Graphic History Collective editor (Between the Lines, 2016)
"Canadian labour history and working-class struggles are brought to life in this anthology of nine short comics, each one accompanied by an informative preface. Each comic showcases the inspiring efforts and determination of working people who banded together with others to fight to change the world. The history of working-class struggle is a fascinating story of conflict and coercion, of resistance and triumph. It has the drama of defeat mixed with the thrill of victory, though not always in equal measure. But, working-class history is not just interesting and exciting; it also contains important lessons for labour and social justice activists today. Illustrate! Educate! Organize! Contributors include Jo SiMalaya Alcampo, Althea Balmes, Christine Balmes, Sam Bradd, Paul Buhle, Nicole Marie Burton, David Camfield, Sean Carleton, Conely de Leon, Robin Folvik, Ethan Heitner, Greg Kealey, Orion Keresztesi, Mark Leier, David Lester, Andrée Lévesque, Zenee May Maceda, Dale McCartney, Doug Nesbitt, Bryan Palmer, Andrew Parnaby, Joan Sangster, Kara Sievewright, Julia Smith, Ron Verzuh, Tania Willard (Secwepemc Nation)"--Publisher